The genus Callitriche (Plantaginaceae: Callitricheae) in South America - Lansdown, Richard V.; Hassemer, Gustavo (Phytotaxa, 2021)
Callitriche is a sub-cosmopolitan plant genus occurring throughout temperate regions of both hemispheres, including the peri-Antarctic islands, with 78 species worldwide. Records of Callitriche include frequent and extensive misidentification due to a combination of factors including a lack of taxonomic and nomenclatural clarification before the mid-20th century. This work aims to contribute to the taxonomic knowledge of the genus Callitriche in South America by presenting taxonomic novelties and a revision of some critical species. More specifically, seven new species are described: C. ciliata, C. concinna, C. dacryoidea, C. ecarinata, C. hegelmaieriana, C. praetermissa and C. schotsmaniana. In addition, C. marginata var. berteroana is here raised to species rank, C. mandonis, C. oblongicarpa and C. turfosa are re-established, and the names C. antarctica, C. deflexa, C. deflexa var. brauniana, C. deflexa var. glaziovii, C. deflexa var. phaeocarpa, C. heterophylla, C. heteropoda, C. terrestris and C. turfosa are typified.